Deep Learning and Machine Learning via a Genetic Algorithm to Classify Breast Cancer DNA Data - Hussein, Noor Alhuda Khalid; Al-Sarray, Basad (Iraqi Journal of Science, 2022)
This paper uses Artificial Intelligence (AI) based algorithm analysis to classify breast cancer Deoxyribonucleic (DNA). Main idea is to focus on application of machine and deep learning techniques. Furthermore, a genetic algorithm is used to diagnose gene expression to reduce the number of misclassified cancers. After patients’ genetic data are entered, processing operations that require filling the missing values using different techniques are used. The best data for the classification process are chosen by combining each technique using the genetic algorithm and comparing them in terms of accuracy.